The Effect of Digital Advertising on Consumer Purchase Intention through Brand Awareness as a Mediating Variable at CV. Tuffero Patisserie, Malang City - Paskalis Puput; Anung Prasetyo Nugroho; Cakti Indra Gunawan; Nur Ida Iriani (International Research & Development for Human Beings (IRDH), 2026)
Digital transformation has shifted marketing strategies towards the use of more measurable and targeted internet-based advertising. This study aims to analyze the effect of Digital Advertising on Purchase Intention with Brand Awareness as a mediating variable at CV. Tuffero Patisserie in Malang City, Indonesia. The urgency of the research is based on the increasing internet penetration and e-commerce activities in Indonesia according to the Central Bureau of Statistics, which encourages SMEs to optimize digital marketing strategies empirically and measurably. The study used a quantitative approach with an explanatory design. The sample consisted of 90 respondents selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0, through outer and inner model testing and bootstrapping at a 5% significance level. The results show that Digital Advertising has a positive and significant effect on Brand Awareness and Purchase Intention. Brand Awareness also has a positive and significant effect on Purchase Intention and partially mediates the relationship between Digital Advertising and Purchase Intention. These findings confirm that the effectiveness of digital advertising not only increases purchase intention directly, but also through strengthening brand awareness. Theoretically, this research enriches the literature on SME digital marketing, and practically provides a strategic basis for optimizing more effective and measurable digital advertising campaigns.